2017
DOI: 10.12806/v16/i4/t2
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Complex Challenges through Adaptive Leadership: A Promising Approach to Collaborative Problem Solving

Abstract: Organizations are faced with solving increasingly complex problems. Addressing these issues requires effective leadership that can facilitate a collaborative problem solving approach where multiple perspectives are leveraged. In this conceptual paper, we critique the effectiveness of earlier leadership models in tackling complex organizational issues. We then examine one promising model, adaptive leadership, in detail and propose that this model provides a leadership approach for addressing current organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
(29 reference statements)
2
27
0
Order By: Relevance
“…The ability of the leader to solve complex problems was investigated and had shown that it indirectly improves the overall outcome of the organisation (Leithwood and Steinbach, 1995). There will be a difference in organisational outcomes when the leaders are able or not able to solve complex problems (Leithwood and Steinbach, 1992;Nelson and Squires, 2017). These findings support the contention that leadership capabilities strongly influence the overall results in the organisation.…”
Section: Leadership Capabilities and Organisational Performancesupporting
confidence: 61%
“…The ability of the leader to solve complex problems was investigated and had shown that it indirectly improves the overall outcome of the organisation (Leithwood and Steinbach, 1995). There will be a difference in organisational outcomes when the leaders are able or not able to solve complex problems (Leithwood and Steinbach, 1992;Nelson and Squires, 2017). These findings support the contention that leadership capabilities strongly influence the overall results in the organisation.…”
Section: Leadership Capabilities and Organisational Performancesupporting
confidence: 61%
“…36 Adaptive leadership enables organizational leaders and staff to develop competencies for supporting patient-centred care: the knowledge, skills and behaviours critical to facilitate new actions and supports. While other leadership approaches, such as transformational leadership, situational leadership, distributed leadership 37 and person-centred leadership, 38 may also enable major shifts in behaviours, roles and relationships, we focus here on adaptive leadership, whose core ideas seem most closely aligned to the changes necessary to move person-centred care from mechanistic to meaningful.…”
Section: What Are Person-centred Care and Adaptive Leadership? How Are These Two Concepts Related?mentioning
confidence: 99%
“…The extended story includes particular skills (e.g., conceptual skills) and behaviors (e.g., task or relationship behaviors) as key characteristics of leaders (Nelson & Squires, 2017;Northouse, 2016). Dugan (2017) classifies these theories that attend to the leader as person-centered theories.…”
Section: Evolution Of Leadership Theorymentioning
confidence: 99%
“…Dugan (2017) classifies these theories that attend to the leader as person-centered theories. Situational DOI: 10.12806/V18/I4/T1 OCTOBER 2019 THEORY 191 approaches to leadership suggest that good leaders change depending on the needs of the situation or context (Antonakis & Day, 2018;Nelson & Squires, 2017;Northouse, 2016). While attention to skills, behaviors, and situations complicate original trait theories, they primarily focus on the aspects of a "leader.…”
Section: Evolution Of Leadership Theorymentioning
confidence: 99%